Antipsychotic Use in Pregnancy and the Risk for Congenital Malformations - Huybrechts, Krista F; Hernández-Díaz, Sonia; Patorno, Elisabetta; Desai, Rishi J; Mogun, Helen; Dejene, Sara Z; Cohen, Jacqueline M; Panchaud, Alice; Cohen, Lee; Bateman, Brian T (JAMA psychiatry (Chicago, Ill.), 2016)
The frequency of antipsychotic (AP) use during pregnancy has approximately doubled during the last decade. However, little is known about their safety for the developing fetus, and concerns have been raised about a potential association with congenital malformations. To examine the risk for congenital malformations overall and cardiac malformations associated with first-trimester exposure to APs. This nationwide sample of 1 360 101 pregnant women enrolled in Medicaid with a live-born infant constituted the pregnancy cohort nested in the Medicaid Analytic Extract database, which included data from January 1, 2000, to December 31, 2010. Participants were enrolled in Medicaid from 3 months before their last menstrual period through at least 1 month after delivery. Relative risks (RRs) were estimated using generalized linear models with fine stratification on the propensity score to control for the underlying psychiatric disorders and other potential confounders. Data were analyzed during 2015. Use of APs during the first trimester, the etiologically relevant period for organogenesis. Major congenital malformations overall and cardiac malformations identified during the first 90 days after delivery. Of the 1 341 715 pregnancies that met inclusion criteria (mean [SD] age of women, 24.02 [5.77] years), 9258 (0.69%) filled at least 1 prescription for an atypical AP and 733 (0.05%) filled at least 1 prescription for a typical AP during the first trimester. Overall, 32.7 (95% CI, 32.4-33.0) per 1000 births not exposed to APs were diagnosed with congenital malformations compared with 44.5 (95% CI, 40.5-48.9) per 1000 births exposed to atypical and 38.2 (95% CI, 26.6-54.7) per 1000 births exposed to typical APs. Unadjusted analyses suggested an increased risk for malformations overall for atypical APs (RR, 1.36; 95% CI, 1.24-1.50) but not for typical APs (RR, 1.17; 95% CI, 0.81-1.68). After confounding adjustment, the RR was reduced to 1.05 (95% CI, 0.96-1.16) for atypical APs and 0.90 (95% CI, 0.62-1.31) for typical APs. The findings for cardiac malformations were similar. For the individual agents examined, a small increased risk in overall malformations (RR, 1.26; 95% CI, 1.02-1.56) and cardiac malformations (RR, 1.26; 95% CI, 0.88-1.81) was found for risperidone that was independent of measured confounders. Evidence from this large study suggests that use of APs early in pregnancy generally does not meaningfully increase the risk for congenital malformations overall or cardiac malformations in particular. The small increase in the risk for malformations observed with risperidone requires additional study.